1997
DOI: 10.4141/a97-006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet and slaughter endpoint on carcass composition and beef quality in Charolais cross steers

Abstract: . 1997. Effect of diet and slaughter endpoint on carcass composition and beef quality in Charolais cross steers. Can. J. Anim. Sci. 77: 403-414. One hundred and eight Charolais cross steers were used to compare forage versus grain feeding as affected by slaughter endpoint on carcass composition and palatability attributes of beef. Diets included a 97% alfalfa silage ration or 68% high moisture corn, 25% alfalfa silage ration from start of test to finish or a ration of 97% alfalfa silage from start of test to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
31
4
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 37 publications
10
31
4
1
Order By: Relevance
“…In contrast, it is generally expected that as cattle age and deposit fat, subcutaneous fat becomes more unsaturated (e.g. Mandell et al 1997). The substantial differences in growth path and age between northern and southern cattle in this study may have contributed to the observed changes in fatty acid composition.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In contrast, it is generally expected that as cattle age and deposit fat, subcutaneous fat becomes more unsaturated (e.g. Mandell et al 1997). The substantial differences in growth path and age between northern and southern cattle in this study may have contributed to the observed changes in fatty acid composition.…”
Section: Discussioncontrasting
confidence: 53%
“…Many studies have shown that increasing weight and fatness can lead to increases in C18:1c9 at the expense of C18:0 (e.g. Mandell et al 1997). It is likely that the changes in fatty acid composition observed in this study may reflect in part differences in fatness between these groups.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In their study, both groups were slaughtered at a similar liveweight (c. 625 kg). In contrast, Mandell et al (1997) reported significantly lower SF for silage-fed yearling Charolais-cross steers compared with animals fed high moisture corn when finished to constant rib fat thickness endpoints. Dubeski et al (1997) concluded that shear force was more sensitive to the rate of gain than to the diet.…”
Section: Tenderness and Consumer Palatability Scoresmentioning
confidence: 76%
“…Another study (Mandell et al 1997) compared Charolais-cross steers finished for 42 days on alfalfa silage then 80 days on a high-grain diet with a similar group finished for 92 days on the high-grain diet. The former group spent 32 days longer in finishing, so were older but had similar carcass weights (314 v. 310 kg) and rib fat depths (7.4 mm), but 17% more intramuscular fat (51.7 v. 44.1 g/kg;…”
Section: Discussionmentioning
confidence: 99%